AB0593 Choroidal Involvement in Systemic Sclerosis: Comparison between Skin Blood Perfusion and Choroidal Thickness before and after Iloprost Treatment. (15th July 2016) - Bernero, E.; Sulli, A.; Ruaro, B.; Trombetta, A.C.; Paolino, S.; Pizzorni, C.; Nicolò, M.; Traverso, C.E.; Cutolo, C.A.
Abstract : Background: Systemic sclerosis (SSc) is characterized by progressive diffuse microvascular damage and decreased blood perfusion (BP) at skin and internal organs (1). Laser speckled contrast analysis (LASCA) evaluate skin BP in different areas of body (2). Histological studies and fluorescein angiography demonstrated choroidal involvement in SSc, and recently optical coherence tomography (OCT) measurement showed significantly thinner choroid thickness (CT) in SSc patients (3–5). Iloprost, a prostacycline analogue, is effective in the treatment of microvascular manifestations in SSc (7). Objectives: To study skin BP and ocular CT in patients with SSc, before and after iloprost treatment. Methods: After informed consent was obtained, twelve SSc patients according to ACR/EULAR classification criteria (8) (mean age 58±13 years, mean disease duration 5±3 years) underwent ophthalmologic evaluation by OCT and BP evaluation by LASCA, before after 8 hours of continuous iloprost i.v. infusion (0.5 ng/kg/min). OCT images were recorded by 3D-2000 OCT (Topcon, Japan) using protocol "line" that averages 50 B-scans and generates a horizontal 6 mm line. CT area measurements were performed manually using image J software. BP was assessed by LASCA at the level of fingertips, periungueal, whole face, perioral and periorbital area, and the average BP calculated as perfusion units (PU)(1). Statistical analysis was performed by non parametric tests. Results: Both before and after iloprost therapy (T0-T1), statistically significant positive correlations between BP and CT were found at periorbital (T0 r=0.55, p=0.022, and T1 r=0.91 p=0.0002), fingertips (T0 r=0.69, p=0.004, and T1 r=0.63, p=0.01), and perioral skin areas (T0 r=0, 75, p=0.002, and T1 r=0, 61, p=0.012). Further correlations were observed at periungueal (T0 r=0.54, p=0.02, and T1 r=0.50, p=0.04) and whole face (T0 r=0.49, p=0.04, and T1 r=0.47, p=0.05). BP was found significantly increased after iloprost therapy in all examined areas (p=0.002). Patients did not show any visual/ocular symptom during and after iloprost infusion. Conclusions: LASCA and OCT seem concordant tools in assessing the functional microvascularization status in SSc patients. Since LASCA is a reliable tool to assess skin BP, its observed correlation with the CT and the effects of iloprost treatment, suggest that the OCT evaluation could be included in periodical instrumental evaluation of SSc progression and effects of microvascular targeted treatments. References: Rosato E, et al Rheumatology 2009;36:2257–63. Ruaro B, et al Ann Rheum Dis 2014;73:1181–5. Farkas TG, et al Am J Ophthalmol 1972;74:875–886. Serup L, et al Ophthalmic Res 1987;19:303–308. Ingegnoli F, et al Microvasc Res 2015;97:31–36. Yamashita T, et al Invest Ophthalmol Vis Sci 2012;53:1102–1107. Scorza R, et al Clin Exp Rheumatol 2001; 19:503–8. Van den Hoogen F, et al. Ann Rheum Dis. 2013;72:1747–55. Disclosure of Interest: None declared